Is palliative care support associated with better quality end-of-life care indicators for patients with advanced cancer? A retrospective cohort study - Ziegler, Lucy E; Craigs, Cheryl L; West, Robert M; Carder, Paul; Hurlow, Adam; Millares-Martin, Pablo; Hall, Geoff; Bennett, Michael I (BMJ open, 2018)
ObjectivesThis study aimed to establish the association between timing and provision of palliative care (PC) and quality of end-of-life care indicators in a population of patients dying of cancer.SettingThis study uses linked cancer patient data from the National Cancer Registry, the electronic medical record system used in primary care (SystmOne) and the electronic medical record system used within a specialist regional cancer centre. The population resided in a single city in Northern England.ParticipantsRetrospective data from 2479 adult cancer decedents who died between January 2010 and February 2012 were registered with a primary care provider using the SystmOne electronic health record system, and cancer was certified as a cause of death, were included in the study.ResultsLinkage yielded data on 2479 cancer decedents, with 64.5% who received at least one PC event. Decedents who received PC were significantly more likely to die in a hospice (39.4% vs 14.5%, P<0.005) and less likely to die in hospital (23.3% vs 40.1%, P<0.05), and were more likely to receive an opioid (53% vs 25.2%, P<0.001). PC initiated more than 2 weeks before death was associated with avoiding a hospital death (≥2 weeks, P<0.001), more than 4 weeks before death was associated with avoiding emergency hospital admissions and increased access to an opioid (≥4 weeks, P<0.001), and more than 33 weeks before death was associated with avoiding late chemotherapy (≥33 weeks, no chemotherapy P=0.019, chemotherapy over 4 weeks P=0.007).ConclusionFor decedents with advanced cancer, access to PC and longer duration of PC were significantly associated with better end-of-life quality indicators.